Coordination between environment, poverty, and SDGs through a carbon tax - Ortega Díaz, Araceli; Guevara, Zeus; Chapa Cantú, Joana (Estudios Económicos de El Colegio de México, 2022)
Since 2014, Mexico has implemented a carbon tax policy, which has not reached the expected revenue, failed at decreasing emissions, and had a regressive effect. Moreover, there has not been coordination between climate and other Sustainable Development Goals (SDGs). To explore this, we perform a Computable General Equilibrium analysis to simulate a coordinated carbon tax policy aimed at reaching the SDGs goals related to poverty, mortality, and education. The results suggest that the required carbon tax rate for approaching SDGs targets by 2030 should be around 15%, which is higher than the actual rate and may cause other distortionary effects.